Impact of the COVID-19 Restrictive Measures on Urban Traffic-Related Air Pollution in Serbia - Malinović-Milićević, Slavica; Doljak, Dejan; Stanojević, Gorica; Radovanović, Milan M. (Frontiers in Environmental Science, 2022)
This study has analyzed the traffic-related change in atmospheric pollutants levels (PM2.5, PM10, CO, NO2, SO2, and O3) caused by the COVID-19 restrictive measures, based on traffic ground-based stations data in urban areas in Serbia. The possible influence of several meteorological factors (temperature, wind, pressure, and humidity), and mobility on the pollutants’ levels were also considered. The obtained results showed a positive correlation of daily NO2 concentrations with mobility and its significant reduction during restrictive measures at all selected monitoring stations. The reduction of NO2 was higher than in other countries (71.1–111.5% for measured, and 49.3–92.6% for ‘deweathered’ data), indicating a high traffic impact on NO2 levels in Serbia. The PM, CO, and SO2 showed a weak correlation with mobility during the period with restrictive measures, which, besides traffic, indicates the significant influence of other sources of their concentration. The O3 concentrations were increased at all measuring stations and are negatively correlated to mobility. Comparison of pollutant concentrations during restriction with the equivalent period in preceding years showed reductions in NO2 and SO2 concentrations. However, compared to previous years, the concentrations of PM2.5, PM10, and CO increased in the period with restrictive measures, indicating lower sensitivity to population mobility and higher dependence on other emission sources. The findings suggest the justification for the use of traffic reduction strategies to improve air quality.